Overview on Patient Centricity in Cancer Care - Narbutas, Šarunas; York, Kristina; Stein, Barry D.; Magsanoc-Alikpala, Kara; Majima, Yoshiyuki; Kalo, Zoltan; Almasi, Timea; Inotai, Andras (Frontiers in Pharmacology, 2017)
Successful implementation of treatment in cancer care partially depends on how patients’ perspectives are taken into account, as preferences of health care professionals and patients may differ. Objectives of this exploratory research were I) to identify patient preferences and values (PPVs) in cancer care as indicated by patient organizations (POs), II) to determine how these PPVs are captured in cancer care guidelines and III) to review how guidelines take into account these PPVs. Based on a survey developed and completed by 19 POs, a literature review was conducted to analyse how patient perspectives are incorporated in oncology treatment guidelines. Based on survey results traditional health technology assessment value propositions of oncology care, such as extended life, treatment-free remission and pain reduction, were also highly rated by POs. However, the heterogeneity of cancer PPVs were clearly reflected in the survey results. PPVs in cancer care guidelines were mostly limited to those micro-level aspects that are strictly related to health care provision, such as side-effects and comorbidities. Patient experience, emotional support and convenience of care were relatively neglected fields in the reviewed guidelines. Patient engagement was rarely presented in the guideline development phase. POs believe that patients should be encouraged to take an active role in their own care due to the heterogeneity of cancer patients and PPVs. Even if patient-centricity is a leading paradigm in cancer policy, based on our research it is not yet standard practice to include patients or POs at all appropriate levels of decision-making processes that are related to their health and well-being. Patient engagement should be an integral part of cancer care decision-making. This complexity must be reflected throughout policy making, avoiding a population level ‘one-size-fits-all’ solution.